Auditors in the financial meltdown: an examination. Issue 4 (5th December 2018) - Sy, Aida; Tinker, Anthony M.
Abstract : Purpose: This paper aims to investigate the financial crises and the role of auditors in those crises. The paper is concerned with the banking system, as the last financial crisis in 2008 was provoked by the mortgage business and the big banks and risks management. Design/methodology/approach: The paper choses to use data from corporations, practices and professional websites. The authors use interviews that were available and related to the subject matter. Academic works are also used to discuss the literature review and various issues. Findings: The paper explores the auditors' responsibilities and finds that there is a growing concern for auditing. This research is complex, as it discovers that corporate executives in the banking business should be more responsible; this is confirmed by the high risks in the financial area that still persists. Research limitations/implications: This is a very complex topic; however, the authors designed it so that it can be read and used by non-accountants, that is to say, CEOs and governmental agencies that are in charge of the regulatory system. Further research studies are needed to ensure ongoing discussions about the financial crisis. The Word is not free from such bad economic events. Practical implications: The contribution is important; this research can be used by organizations, governments and academics. Social implications: The paper includes implications for the banking and auditing industries. It extends to the public interest. Originality/value: This paper contributes to the literature for academic and can be used for teaching purposes. Students can understand the paper, as the authors did not use a regression model.